2019
DOI: 10.3390/w11020189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ENSO on Temperature, Precipitation, and Potential Evapotranspiration of North India’s Monsoon: An Analysis of Trend and Entropy

Abstract: The influence of El Niño Southern Oscillation (ENSO) on the north Indian temperature, precipitation, and potential evapotranspiration (PET) change patterns were evaluated during the monsoon season across the last century. Trends and shifts in 146 districts were assessed using nonparametric statistical tests. To quantify their temporal variation, the concept of apportionment entropy was applied to both the annual and seasonal scales. Results suggest that the El Niño years played a greater role in causing hydro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 78 publications
(104 reference statements)
0
24
1
1
Order By: Relevance
“…To account for the autocorrelations or persistence, a series of modified versions of MK trend test were proposed (i.e., MK2, MK3 and MK4). Some studies have shown that the modified MK models were more effective for the variables with a considerable autocorrelation [63]. However, there was a neglectable autocorrelation in the data used in this study; consequently, the autocorrelation or persistence has few influences on the datasets.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…To account for the autocorrelations or persistence, a series of modified versions of MK trend test were proposed (i.e., MK2, MK3 and MK4). Some studies have shown that the modified MK models were more effective for the variables with a considerable autocorrelation [63]. However, there was a neglectable autocorrelation in the data used in this study; consequently, the autocorrelation or persistence has few influences on the datasets.…”
Section: Methodsmentioning
confidence: 74%
“…Sen's method was adopted to quantify the magnitude of the trends [61], as it is a non-parametric approach, and is appropriate in conjunction with the MK test. Moreover, Sen's method is not affected by outliers as it determines the median slope of all possible pairs, which makes the test robust against possible outliers [63]. The Kriging interpolation method was used to analyze the spatial distribution of each rainfall indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Within the focus of the paper, the simultaneous effects of ENSO on T, P and EV during Monsoon season over the last century for 146 districts across North India were thoroughly investigated in [33]. Results suggest that El Niño years have a significant influence on hydro-climatic variables in comparison to La Niña or neutral years and most of the district experienced a significant decreasing trend in T, P and EV variable across the century.…”
Section: Impact Of Climate Change On Enso Eventsmentioning
confidence: 99%
“…Climate change has significantly altered the hydrological processes like floods and droughts [4] that obstruct the functioning of the natural ecosystem, which results in more frequent but unlikely extreme events. Additionally, oceanic variabilities like El Niño-Southern Oscillation also influence the hydrology of the region [5,6]. The average surface temperature of the United States (U.S.) has risen at a rate of 255.45 K/decade since 1901 [7].…”
Section: Introductionmentioning
confidence: 99%